Low‐dose, continuous enzyme replacement therapy ameliorates brain pathology in the neurodegenerative lysosomal disorder mucopolysaccharidosis type IIIA. Issue 3 (24th February 2016) - King, Barbara; Hassiotis, Sofia; Rozaklis, Tina; Beard, Helen; Trim, Paul J.; Snel, Marten F.; Hopwood, John J.; Hemsley, Kim M.
Abstract: Repeated replacement of sulphamidase via cerebrospinal fluid injection is an effective treatment for pathological changes in the brain in mice and dogs with the lysosomal storage disorder, mucopolysaccharidosis type IIIA (MPS IIIA). Investigational trials of this approach are underway in children with this condition, however, infusions require attendance at a specialist medical facility. We sought to comprehensively evaluate the effectiveness of sustained‐release (osmotic pump‐delivered) enzyme replacement therapy in murine MPS IIIA as this method, if applied to humans, would require only subcutaneous administration of enzyme once the pump was installed. Six‐week‐old MPS IIIA and unaffected mice were implanted with subcutaneous mini‐osmotic pumps connected to an infusion cannula directed at the right lateral ventricle. Either recombinant human sulphamidase or vehicle were infused over the course of 7 weeks, with pumps replaced part‐way through the experimental period. We observed near‐normalisation of primarily stored substrate (heparan sulphate) in both hemispheres of the MPS IIIA brain and cervical spinal cord, as determined using tandem mass spectrometry. Immunohistochemistry indicated a reduction in secondarily stored GM 3 ganglioside and neuroinflammatory markers. A bias towards the infusion side was seen in some, but not all outcomes. The recombinant enzyme appears stable under pump‐like conditions for at least 1 month. Given that infusion pumps are in clinical use in other nervous system disorders, e.g. for treatment of spasticity or brain tumours, this treatment method warrants consideration for testing in large animal models of MPS IIIA and other lysosomal storage disorders that affect the brain. Clinical trials of repeated injection of replacement enzyme into CSF are underway in patients with the inherited neurodegenerative disorder mucopolysaccharidosis type IIIA. In this pre‐clinical study, we examined an alternative approach – slow, continual infusion of enzyme using pumps. We observed significant reductions in substrate accumulation and other disease‐based lesions in treated mouse brain. Thus, the strategy warrants consideration for testing in large animal models of MPS IIIA and also in other neurodegenerative lysosomal storage disorders. Abstract : Clinical trials of repeated injection of replacement enzyme into CSF are underway in patients with the inherited neurodegenerative disorder mucopolysaccharidosis type IIIA. In this pre‐clinical study, we examined an alternative approach – slow, continual infusion of enzyme using pumps. We observed significant reductions in substrate accumulation and other disease‐based lesions in treated mouse brain. Thus, the strategy warrants consideration for testing in large animal models of MPS IIIA and also in other neurodegenerative lysosomal storage disorders.